SETS-BASED PHYSICS MODULES INTEGRATED WITH LOCAL POTENTIALS TO IMPROVE SCIENCE PROCESS SKILLS - Siti Sarah; Dewi Istiyatun Khasanah; Arif Maftukhin; Irma Dwi Tantri; Maghfira Febriana (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
This research aims to produce science, technology, and society (SETS)-based physics modules integrated with local potential to improve science process skills that are valid, practical, and effective. The research method is Research and Development using the Borg & Gall model with 10 (ten) steps. However, this study only carried out steps 1 to 7, namely (1) determining potential and problems, (2) collecting data, (3) compiling product designs, (4) validating, (5) revising, and (6) preliminary research, and (7) analyze the results of preliminary research. The research produced a SETS-based physics module integrated with valid and practical local potential in improving science process skills. The validation scores of material experts and media experts show 77.8% (valid) and 80.6% (valid). Assessment of practitioners, namely physics teachers and high school students showed 91.2% (valid) and 85.4% (valid). The results of the study showed that there were significant differences in the students' science process skills before and after using the SETS-based Physics module integrated with local potential. Students experience an increase in science process skills by 64% with moderate criteria.